Mapping of the gene in tomato conferring resistance to root-knot nematodes at high soil temperature - Devran, Zübeyir; Özalp, Tevfik; Studholme, David J.; Tör, Mahmut (Frontiers in Plant Science, 2023)
Root-knot nematodes (RKNs, Meloidogyne spp.) can cause severe yield losses in tomatoes. The Mi-1.2 gene in tomato confers resistance to the Meloidogyne species M. incognita, M. arenaria and M. javanica, which are prevalent in tomato growing areas. However, this resistance breaks down at high soil temperatures (>28 °C). Therefore, it is imperative that new resistance sources are identified and incorporated into commercial breeding programmes. We identified a tomato line, MT12, that does not have Mi-1.2 but provides resistance to M. incognita at 32ºC soil temperature. An F2 mapping population was generated by crossing the resistant line with a susceptible line, MT17; the segregation ratio showed that the resistance is conferred by a single dominant gene, designated RRKN1 (Resistance to Root-Knot Nematode 1). The RRKN1 gene was mapped using 111 Kompetitive Allele Specific PCR (KASP) markers and characterized. Linkage analysis showed that RRKN1 is located on chromosome 6 and flanking markers placed the locus within a 270 kb interval. These newly developed markers can help pyramiding R-genes and generating new tomato varieties resistant to RKNs at high soil temperatures.